Newer Aspects in Phototherapy - Sekar, C.S.; Srinivas, C.R. (Nepal Journal of Dermatology, Venereology & Leprology, 2016)
The concept of phototherapy has undergone a lot of changes in the past 30 years. It started with the emergence of psoralen ultraviolet A (PUVA) for the treatment of psoriasis. The subsequent evolution of Narrow band UVB therapy, Targeted phototherapy, UVA1 therapy, Home phototherapy and the use of LED lamps have revolutionized the treatment of various skin diseases. This article briefly summarizes the advances made in the last few years in the field of phototherapy. Nepal Journal of Dermatology, Venereology & Leprology, Vol.14(1) 2016, pp.5-8